Cellulomonas palmilyticum sp. nov., from earthworm soil biofertilizer with the potential to degrade oil palm empty fruit bunch. Issue 8 (12th August 2022) - Siriatcharanon, Ake-kavitch; Sutheeworapong, Sawannee; Waeonukul, Rattiya; Pason, Patthra; Uke, Ayaka; Kosugi, Akihiko; Ratanakhanokchai, Khanok; Tachaapaikoon, Chakrit
Abstract : Oil palm empty fruit bunch (OPEFB) is lignocellulosic waste from the palm oil industry in Southeast Asia. It is difficult to degrade because of its complex matrix and recalcitrant structure. To decompose OPEFB, highly efficient micro-organisms and robust enzymatic systems are required. A bacterium with high degradation ability against untreated OPEFB was isolated from earthworm soil biofertilizer and designated as strain EW123 T . Cells were Gram-stain-positive, rod-shaped and catalase-positive. In tests, the strain was negative for mycelium formation, motility, nitrate reductase and urease. The 16S rRNA gene analysis of the isolate showed 98.21 % similarity to Cellulomonas uda NBRC 3747 T, whereas similarity to other species was below 98 %. The genome of strain EW123 T was 3 834 009 bp long, with 73.97 mol% G+C content. Polar lipid analysis of strain EW123 T indicated phosphatidylglycerol, phosphatidylethanolamine, diphosphatidylglycerol and aminophospholipid as the lipid components of the cell wall. The major cellular fatty acid was anteiso-C15 : 0 (41.26 %) and the isomer of 2, 6-diaminopimelic acid (DAP) was meso -DAP. The average nucleotide identity value between the genome sequences of EW123 T and C. uda NBRC 3747 T was 88.6 %. In addition, the digital DNA–DNA hybridization and genome average amino acid between those strains were 36.1 and 89.68 %, respectively. The ORF number (186) of carbohydrate-active enzymes, including cellulases, xylanases, mannanase, lipase and lignin-degrading enzymes, was higher than those of related strains. These results indicate that the polyphasic characteristics of EW123 T differ from those of other related species in the genus Cellulomonas . We therefore propose a novel species of the genus Cellulomonas, namely Cellulomonas palmilyticum sp. nov. (type strain TBRC 11805 T =NBRC 114552 T ), with the ability to effectively degrade untreated OPEFB.